Towards an Open Infrastructure for Relating Scholarly Assets. - MUNRO, Christopher; COUCH, Philip; JOHNSON, Jon; AINSWORTH, John; BUCHAN, Iain (Studies in Health Technology & Informatics, 2017)
Discovery of useful relationships between scholarly assets on the web is challenging, both in terms generating the right metadata around the assets, and in connecting all relevant digital entities in chain of provenance accessible to the whole community. This paper reports the development of a framework and tools enabling scholarly asset relationships to be expressed in a standard and open way, illustrated with use-cases of discovering new knowledge across cohort studies. The framework uses Research Objects for aggregation, distributed databases for storage, and distributed ledgers for provenance. Our proposal avoids management by a single central platform or organization, instead leveraging the use of existing resources and platforms across natural partnerships. Our proposed infrastructure will support a wide range of users from system administrators to researchers.